Ambedkar, Gandhi and empowerment of dalit - Pathak, Narendra (New Delhi World Heritage Inc, 2023)
If we look to the history of Dalit movement, it is as old as the birth of the concept of untouchability, which was the darkest spot in Hindu social structure. It is known history that Dr. B.R. Ambedkar$1 (Bs intense struggle against the British rulers and the Indian society and its leaders resulted in recognizing for the first time the political rights of dalits in the Communal Award of 1932 given by PM Ramsay MacDonald after the debates and decisions of the Round Table Conferences. Like other communities, dalits were also given separate electorates to send their representatives to the central and provincial assemblies. With this the political and social identity of the dalits got established. The Hindu society and its leaders led by Mahatma Gandhi were dead against this happening. It is indeed to note that even after seventy two years of our Independence and Universal Declaration of Human Rights, the empowermentofdalits in general and dalit girls in particular, the field of education remains unsatisfactory. The various schemes and policies have failed in accelerating and retaining the dalit in education sector. This book is an effort to understand ambedkar and gandhi$1 (Bs stand and efforts on dalit empowerment. A good read book for students, social workers and all interested in dalit issues and empowerment.s
Keywords: B. R. Ambedkar; Mahatma Gandhi; Empowerment of Dalit